'STEM girls should be': a discourse analysis of school structures and their impact on African American, middle school girls' positioning in science. Issue 6 (2nd November 2021) - Wade-Jaimes, Katherine
ABSTRACT: This paper explores school structure in an all-girls, predominantly African American middle class school to examine the ways in which discourses of education, race, gender, and science work to position middle school, African American girls as outside of science. Using discourse analysis, two prominent school signs are presented, a bulletin board and a classroom sign, and examined alongside excerpts from student interviews. The results indicate that being a 'Nice Girl' is a prerequisite for being a 'Good Student' and is synonymous with being a 'STEM Girl', potentially alienating students from viewing themselves, or wishing to be viewed by others, as a science person.